-5z=-z-4z

Simple and best practice solution for -5z=-z-4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5z=-z-4z equation:


Simplifying
-5z = -1z + -4z

Combine like terms: -1z + -4z = -5z
-5z = -5z

Add '5z' to each side of the equation.
-5z + 5z = -5z + 5z

Combine like terms: -5z + 5z = 0
0 = -5z + 5z

Combine like terms: -5z + 5z = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3n+n-8=39 | | y=6x^2-12x+10 | | x^4-32x^2=2x+3 | | 10x=12.2222222 | | 7b=6 | | 75+5x-5+4x+2=180 | | -2t=9-t | | -8x+10+9x=3+x+7 | | 0.3(x-5)=0.3x+8-2+0.5 | | 4-2x-3=16 | | 1.5n=1.5 | | -19-14j=6-9j | | ax+y=10 | | -u+5=-17-18u+19u | | -4.4=0.08-0.2r | | (1-i)x-(3-i)=0 | | 16-20f=-18f | | 5x+10-30=7x-500+150 | | 8m=-10+10m | | -h-10=h+6 | | 24.33333333+-2.333333333y+4x+23=180 | | 4(5(-8)+4)=9((-8)-8) | | -10+2y=8+4y | | 7(y+1)=6y-9 | | Ht=-16t^2+35+ho | | -8t=-3-5t | | 18y-405=99 | | 10-b=9b-10 | | 4c-2=8c-10 | | 2+8=-5(6x-2) | | -p=-7-2p | | 9x-38+21y-1=180 |

Equations solver categories